BEYOND COMPLIANCE, ANTARA PENGHARGAAN DAN PERILAKU BISNIS ETIS STUDI KASUS: PROPER PERINGKAT EMAS LINGKUNGAN HIDUP - Andriya Risdwiyanto (Universitas Muhammadiyah Semarang, 2015)
This study was conducted to provide answers and explanations for the emergence of two fundamental questions. First, how the state of society and the environment around the operating company ratingsgold rank of PROPER. Second, what people's expectations for the company's operating processes of PROPER winning gold rank. This study was designed using an inductive approach and qualitative methods. Researchers used a single case study method to get further and comprehensive explanation associated with companies that obtain and able to maintain a gold ranking PROPER-based of theMinistry of Environment of the Republic of Indonesia for the last two consecutive years. Based on the exploration of this case study, researchers compiled based company management model of environmental awareness in an effort to realize the expectations of society, namely Bumi Ayu danMasyarakat Rahayu (BAMR) means the Beautiful Planet and Prosperity People. Based on the exploration of this case study, researchers compiled based company management model of environmental awareness in an effort to realize the expectations of society. The model is Bumi Ayu dan Masyarakat Rahayu (BAMR Model) means the Beautiful Earth and the Prosperity People. This studyexplored BAMR Model which determined by the following components: (1) Awareness or maturity of the company, (2) Recognition and standardization, (3) Orientation of stakeholders’ interests, (4) The Alignment of social and economic aspects, (5) Compliance with the law, (6) Business ethics, and (7)Harmonization. Key Words: Social Responsibility, Environment, PROPER